Making information skills meaningful: a case study from occupational therapy. (23rd February 2018) - Spring, Hannah
Abstract: The effective delivery of information literacy training can be a challenging process, and health library and information professionals are constantly innovating in this area. This article presents a case study of the BHSc (Hons) Occupational therapy degree programme at York St John University to demonstrate ways in which deep integration of information skills into the curriculum can be achieved. The article advises that in the delivery of health and social care related information skills, we should look more broadly at where relevant learning can happen. In particular, contexts of the health care environment are suggested as a consideration rather than the narrow scope of the academic, classroom‐based environment. Examples are provided of specific teaching and learning activities used on the programme alongside CPD activity and curriculum design.